2021
DOI: 10.1016/j.hroo.2021.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of sustained fetal tachyarrhythmias after transplacental treatment

Abstract: Background Fetal tachyarrhythmia is a condition that may lead to cardiac dysfunction, hydrops, and death. Despite a transplacental treatment, failure to obtain or maintain sinus rhythm may occur. Objective We aimed to analyze the perinatal outcomes of sustained fetal tachyarrhythmias after in utero treatment. Methods We performed a retrospective evaluation of 69 cases with sustained fetal tachyarrhythmia. We compared the perinatal and long-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
(46 reference statements)
0
13
0
Order By: Relevance
“…Parents and caregivers require education on the identification and management of SVT, as well as the signs and symptoms of distress, before discharge from the hospital to improve outcomes for the infant and decrease parental anxiety (Table 4). 11,17,45,64 Many newborns with prior fetal SVT will be discharged on an antiarrhythmic, which requires additional education. Mobile cardiac telemetry at the time of discharge can be helpful for parents who are already dealing with a newborn's physical needs, medication administration, and other issues.…”
Section: Role Of the Nurse Specialist In Neonatal Arrhythmiasmentioning
confidence: 99%
“…Parents and caregivers require education on the identification and management of SVT, as well as the signs and symptoms of distress, before discharge from the hospital to improve outcomes for the infant and decrease parental anxiety (Table 4). 11,17,45,64 Many newborns with prior fetal SVT will be discharged on an antiarrhythmic, which requires additional education. Mobile cardiac telemetry at the time of discharge can be helpful for parents who are already dealing with a newborn's physical needs, medication administration, and other issues.…”
Section: Role Of the Nurse Specialist In Neonatal Arrhythmiasmentioning
confidence: 99%
“…Studies have reported that AF patients need a longer treatment duration to convert to sinus rhythm, but once cardioversion is achieved, it is not easy to relapse [10][11]. In this case, the patient was treated with oral digoxin for 22 days.…”
Section: Discussionmentioning
confidence: 97%
“…Research has reported that patients with AF need a longer treatment duration to convert to sinus rhythm. However, once cardioversion is achieved, relapses are not frequent (Bartin et al, 2021; Lisowski et al, 2000). An interesting case report shared the experience of two preterm babies with AF associated with maternal opiate abuse.…”
Section: Discussionmentioning
confidence: 99%